S-LOCUS EARLY FLOWERING 3 Is Exclusively Present in the Genomes of Short-Styled Buckwheat Plants that Exhibit Heteromorphic Self-Incompatibility - Yasui, Yasuo; Mori, Masashi; Aii, Jotaro; Abe, Tomoko; Matsumoto, Daiki; Sato, Shingo; Hayashi, Yoriko; Ohnishi, Ohmi; Ota, Tatsuya (PLOS ONE, 2012)
The different forms of flowers in a species have attracted the attention of many evolutionary biologists, including Charles Darwin. In Fagopyrum esculentum (common buckwheat), the occurrence of dimorphic flowers, namely short-styled and long-styled flowers, is associated with a type of self-incompatibility (SI) called heteromorphic SI. The floral morphology and intra-morph incompatibility are both determined by a single genetic locus named the S-locus. Plants with short-styled flowers are heterozygous (S/s) and plants with long-styled flowers are homozygous recessive (s/s) at the S-locus. Despite recent progress in our understanding of the molecular basis of flower development and plant SI systems, the molecular mechanisms underlying heteromorphic SI remain unresolved. By examining differentially expressed genes from the styles of the two floral morphs, we identified a gene that is expressed only in short-styled plants. The novel gene identified was completely linked to the S-locus in a linkage analysis of 1,373 plants and had homology to EARLY FLOWERING 3. We named this gene S-LOCUS EARLY FLOWERING 3 (S-ELF3). In an ion-beam-induced mutant that harbored a deletion in the genomic region spanning S-ELF3, a phenotype shift from short-styled flowers to long-styled flowers was observed. Furthermore, S-ELF3 was present in the genome of short-styled plants and absent from that of long-styled plants both in world-wide landraces of buckwheat and in two distantly related Fagopyrum species that exhibit heteromorphic SI. Moreover, independent disruptions of S-ELF3 were detected in a recently emerged self-compatible Fagopyrum species and a self-compatible line of buckwheat. The nonessential role of S-ELF3 in the survival of individuals and the prolonged evolutionary presence only in the genomes of short-styled plants exhibiting heteromorphic SI suggests that S-ELF3 is a suitable candidate gene for the control of the short-styled phenotype of buckwheat plants.